Clonagem e expressão da nucleoproteína (NP) e da glicoproteina hemaglutinina-neuraminidase (HN) do vírus da doença de Newcastle (VDN) para aplicação na detecção de anticorpos específicos pelo método indireto de ELISA - Silva, K. R.; Gonçalves, M. C. M.; Montassier, M. F. S.; Fernandes, C. C.; Oliveira, E. S.; Montassier, H. J. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Newcastle disease (ND) is one of the most important disease for the poultry industry worldwide. Newcastle disease virus (NDV) is the causative agent and usually induces severe lesions in respiratory and digestive tracts, requiring increasingly rapid and effective techniques for the laboratory diagnosis. NDV virions are made of three envelope and three core structural proteins, from which the major antigens were identified; as the haemagglutinin-Neuraminidase (HN) envelope glycoprotein and nucleocapside (NP) protein. The HN glycoprotein is involved in virus attachment to the host cell receptors and contains relevant virus-neutralizing and haemagglutinating-inhibitor epitopes. The nucleocapside protein (NP) of NDV has highly conserved amino acid sequences, and a high immunogenicity. Several methods have been investigated for the laboratory diagnosis of NDV infection, including serological tests, such as haemagglutination inhibition (HI) assays and conventional ELISA methods which depend on laborious and time-consuming procedures of virus propagation in SPF embryonated chicken eggs, and the purification of virus particles to be adsorbed to the microplate solid phase. This study aimed to clone the full open reading frame of NP gene, and the 5’-part and 3’-part of HN gene of NDV in a heterologous system (Escherichia coli), using pETSUMO vector in order to express the NP protein, or the amino and carboxy-terminal parts of HN glycoprotein for using in NDV immunodiagnosis. The NP and the amino and carboxy-terminal fragments of HN glycoprotein were expressed as fusion recombinant proteins containing SUMO peptide and poly-histidine tags. These proteins after purification in nickel-agarose resin, and biochemical and immunochemically characterization by SDS-PAGE and Western-blotting, demonstrated the ability to be recognized by polyclonal antibodies form SPF chickens infected with LaSota strain of NDV. The NP and amino and carboxy-terminal fragments of HN glycoprotein were used to develop indirect ELISA methods for using in chicken antibody detection. The assays were evaluated with a panel of 120 chicken serum samples. The results showed comparable agreement, specificity and sensitivity.